Climate-neutral and Smart Cities: a critical review through the lens of environmental justice - Beretta, Ilaria; Bracchi, Caterina (Frontiers in Sociology, 2023)
The political choices made by the European institutions in the last twenty years show how the conviction is increasingly rooted that the management of environmental problems and, more specifically, the fight against climate change can find a valid solution in technology and ecoinnovations. This is evident starting from the last two growth strategies adopted (Europe 2020 and the European Green Deal), from the long series of measures implemented to put them into practice and from the main R&I funding programmes, such as Horizon Europe. In this context, the problem of justice and inclusiveness of the various initiatives implemented is attracting growing attention. In fact, if the institutional documents assume that green and smart participated projects are also fair and inclusive, a growing body of literature based on empirical studies seems to refute this assumption. Within this framework, the present work analyses first the critical literature and then the three main preparatory documents for the Horizon Europe Mission Climate-neutral and Smart Cities, which selected 100 European cities to become climate-neutral by 2030. These have been studied through the lens of environmental justice, in order to assess the European Commission's understanding of the existing and arising equity issues in the path towards climate neutrality. The research shows that, while the first two documents seemed informed by the idea that participation automatically translates into equality, the last guidelines show a deeper acknowledgement of the multidimensional nature of environmental justice. One that, beyond participation, also considers issues of distribution, rights, responsibilities and recognition. The present work should nevertheless be understood as a preparatory, analytical tool that will require the further definition and implementation of Climate City Contracts by the selected cities, in order to assess how the issue of environmental justice is effectively being considered in each specific context.